Exploring Gender Inequalities and Promoting Equal Opportunities in Ghana's Cocoa Industry Using Harvard Analytical Framework - Enoch Kwame Tham-Agyekum; Anthony Appiah; Fred Ankuyi; Gifty-Maria Sangber-Dery; Cherita Antwi; Kaakyire Opoku Acheampong; Tania Akolgo; Tetteh Adesah; John-Eudes Andivi Bakang (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Using the Harvard Analytical Framework, this study explores the gender inequalities among cocoa farmers in Southern Ghana and also recommends strategies for promoting equal opportunities between the farmers. Specifically, the research identifies and describes the productive, reproductive, and community-based roles within these communities, explores access and control of resources, services, and decision-making processes and ascertains the factors that influence cocoa farmers' gendered opportunities or constraints. We used a cross-sectional survey design approach to select 232 respondents via the multi-stage sampling technique. Data was analysed using mainly descriptive statistics. The study reveals that although men and women cocoa farmers play useful roles in cocoa production, differences exist in their experiences. While men dominate in all the productive roles and some community-based roles, women dominate in the majority of the reproductive roles. Men have more access to and control over resources, services, and decision-making processes. Community norms, political, religious, and social factors serve as gendered opportunities for farmers, while economic factors are gendered opportunities and constraints. The study recommends the promotion of gender-responsive agricultural training that will aim to empower women to engage in productive roles. Policies and interventions that facilitate women’s access and control over essential resources such as land, inputs, and finances must be implemented by the Ghana Cocoa Board